Perancangan Website UMKM Roti Bakar Lava Toast Menggunakan Visual Studio Code Untuk Pengembangan Pemasaran dan Promosi - Dian Rahmadani; Muthia Regina Jhonstin; Naufal Restu Perdana; Alfatah Haries; Faradika (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
marketing and promotion. The methods used include data collection through interviews with the owner and direct observation at the Roti Bakar Lava Toast location, followed by designing the database, appearance, and structure of the website. The results of this implementation are in the form of a website https://lavatoastgor.github.io/lavatoastpdggor/. From this design, it shows that the website developed functions as an effective digital storefront, providing complete information about the product, and facilitating interaction with consumers. The conclusion of this project states that the implementation of this website is expected to increase the existence of Lava Toast Products in the digital market, expand consumer reach, and support business sustainability.